2015
DOI: 10.1055/s-0035-1558152
|View full text |Cite|
|
Sign up to set email alerts
|

Prinzip Gegenparese: M.-obliquus-inferior-Rücklagerung bei Patienten mit endokriner Orbitopathie

Abstract: Inferior oblique muscle recession can be very successfully performed on the contralateral eye in patients with mild inferior rectus muscle fibrosis. Surgery at the contralateral yoke muscle prevents the risk of overeffect with resulting diplopia in downgaze, which could occur if small distance recession had been performed at the inferior rectus muscle. An overeffect in relation to inferior oblique recession will only cause diplopia in upgaze, which is much less troublesome in daily routine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Another approach, large inferior recessions and tendon elongations can be associated with incyclotorsion. Therefore, they should be considered preferably in cases with excyclotorsions (Eckstein et al 2012;Jellema et al 2012). When using the combined approach, the simultaneously performed contralateral superior recession can neutralize this incyclotorsion.…”
Section: Surgical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another approach, large inferior recessions and tendon elongations can be associated with incyclotorsion. Therefore, they should be considered preferably in cases with excyclotorsions (Eckstein et al 2012;Jellema et al 2012). When using the combined approach, the simultaneously performed contralateral superior recession can neutralize this incyclotorsion.…”
Section: Surgical Resultsmentioning
confidence: 99%
“…De Hoog et al have shown that this condition occurs with ipsilateral superior rectus muscle fibrosis (De Hoog et al 2010). In this condition, an inferior oblique recession in the contralateral eye (Eckstein et al 2015) or an asymmetrical inferior rectus recession would be a better option (Jellema et al 2012).…”
Section: Surgical Resultsmentioning
confidence: 99%
See 2 more Smart Citations